2011
DOI: 10.1161/hypertensionaha.110.167775
|View full text |Cite
|
Sign up to set email alerts
|

Linking Oxidative Stress, the Renin-Angiotensin System, and Hypertension

Abstract: See related article, pp 452-459T he involvement of oxidative stress in hypertension and in renal and cardiovascular diseases has been intensely studied since the early 1990s. Oxidative stress has been implicated in chronic kidney disease, 1 endothelial damage, atherosclerosis, 2 and myocardial disease, 3 whereas the administration of antioxidants, such as Tempol 4 and N-acetyl cysteine, 1 has been shown to exert a protective effect against these conditions. Nevertheless, the molecular mechanisms and intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 11 publications
0
33
0
1
Order By: Relevance
“…Collectively, these data support our hypothesis that increased RAAS activity in hypertension exaggerates skeletal muscle contraction-evoked reflex sympathoexcitation by inducing oxidative stress in the muscle. Increased RAAS activity and developed oxidative stress are involved in the pathogenesis of hypertension (12,26,55) and are a hallmark in cardiovascular diseases that often develop from prolonged hypertension. In heart failure, we (19) have previously demonstrated that oxidative stress in the muscle plays a role in exaggerating the exercise pressor reflex.…”
Section: H148mentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these data support our hypothesis that increased RAAS activity in hypertension exaggerates skeletal muscle contraction-evoked reflex sympathoexcitation by inducing oxidative stress in the muscle. Increased RAAS activity and developed oxidative stress are involved in the pathogenesis of hypertension (12,26,55) and are a hallmark in cardiovascular diseases that often develop from prolonged hypertension. In heart failure, we (19) have previously demonstrated that oxidative stress in the muscle plays a role in exaggerating the exercise pressor reflex.…”
Section: H148mentioning
confidence: 99%
“…The activity of the renin-angiotensin-aldosterone system (RAAS) is increased in hypertension (12). ANG II, an effector molecule of the RAAS, plays an important role in developing and maintaining hypertension by constricting vessels via its action on smooth muscle cells (5,14).…”
mentioning
confidence: 99%
“…This pathway also involves NADPH oxidase (NOX)-dependent mitochondrial reactive oxygen species (ROS) release, which itself activates the p90 RSK -NHE-1 redoxsensitive kinase, among others (for review, see Ref. [22]). Recently, Nakamura et al [40] demonstrated in vitro that NHE-1 hyperactivity is sufficient to generate Ca +2 signals required for CH to take place.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the information gathered from many clinical literature reports supplemented with in vivo experiments suggests that the biology of the RAS or ANG II, oxidant stress, and inflammatory cytokines is intertwined such that the pathological effects manifest in all the compartments of the kidney, like in chronic kidney disease, such as diabetic nephropathy and tubulointerstitial fibrosis (47,53,75). Interestingly, the oxidant stress whether originating because of inflammation or ANG II stimulation can upregulate ANG II type 1 receptor (AT 1 R) with a multitude of responses, including activation of signaling pathways and transcription factors (6,18). One of the important transcription factors that is induced by ANG II or following AT 1 R or AT 2 R upregulation or activation of small GTPase (Rho-kinase) seems to be NF-B.…”
Section: Discussionmentioning
confidence: 99%